What even is gender? - Briggs, R. A. 1982-; George, B. R. (Routledge, Taylor & Francis Group, 2023)
Debates about gender are everywhere. Is it an inner identity, a biological fact, or an oppressive system? Should we respect it or resist it? What Even Is Gender? shifts the conversation in a fresh direction, arguing that these debates rest on a shared mistake: the idea that there is one thing called "gender" that both sides are arguing about. The authors distinguish a range of phenomena that established vocabulary often lumps together. This sheds light on the equivocations and false dichotomies of "gender" talk, and how they deny many of us the tools to make our needs, experiences, and concerns intelligible to others or even to ourselves. The authors develop a conceptual toolkit that helps alleviate the harms that result from the limitations of familiar approaches. They propose a pluralistic concept of "gender feels" that distinguishes among our experiences of diverse facets of gendered life. They develop a flexible approach to gender categories that reflects the value of self-determination. And they suggest that what we need is not one universal language of gender, but an awareness of individual variation and a willingness to adjust to changing contexts and circumstances. A bold and thought-provoking approach to thinking about gender, What Even Is Gender? will be of great interest to those in philosophy, gender studies, sociology, and LGBTQIA+ studies"--